volume of the box is 675 cubic inches
A machine produces open boxes using square sheets of plastic.
It is a square sheet so length and width are same
Lets assume length as x so width is also x
The machine cuts equal-sized squares measuring 3 inches on a side from each corner of the sheet.
After turning up the sides the height of the box becomes 3 inches
We know the volume of a box formula
Volume = Length * width * height
We know length is x , width is x and height = 3
So V = x * x * 3
Given volume = 675 cubic inches
![675 = x * x * 3](https://tex.z-dn.net/?f=675%20%3D%20x%20%2A%20x%20%2A%203)
![675 = x^2* 3](https://tex.z-dn.net/?f=675%20%3D%20x%5E2%2A%203)
Divide by 3 on both sides
![225 = x^2](https://tex.z-dn.net/?f=225%20%3D%20x%5E2)
Now we take square root on both sides
x = 15
the length of one side of the open box is 15 inches.
Answer:
A B and E
Step-by-step explanation:
Answer:
Step-by-step explanation:
While working at his neighborhood math tutoring center researching the comprehension level of the students Dion investigated that the distribution of the student test scores are normally distributed with a mean of 79.13 and a standard deviation of 6.34. What is the probability that the student scores less than 60.11
We solve using z score formula
z = (x-μ)/σ, where x is the raw score, μ is the population mean, and σ is the population standard deviation.
z = 60.11 - 79.13/6.34
You can group first two conjunctions and second two:
![x^3 - 9x^2 + 5x - 45=(x^3-9x^2)+(5x-45)](https://tex.z-dn.net/?f=x%5E3%20-%209x%5E2%20%2B%205x%20-%2045%3D%28x%5E3-9x%5E2%29%2B%285x-45%29)
.
In first brackets you have common
![x^2](https://tex.z-dn.net/?f=x%5E2)
and in second brackets common is 5:
![(x^3-9x^2)+(5x-45)=x^2(x-9)+5(x-9)=(x-9)(x^2+5)](https://tex.z-dn.net/?f=%28x%5E3-9x%5E2%29%2B%285x-45%29%3Dx%5E2%28x-9%29%2B5%28x-9%29%3D%28x-9%29%28x%5E2%2B5%29)
.
Answer:
2,5
Step-by-step explanation:
2,5 is just one of the many solutions to this problem. you can just take a random number for x, for example 2. your equation will look like this 3(2)-y=1. now you just solve for y. 3x2=6. 6-1=5. so y=5.